Research on hydrogen production and degradation of corn straw by circular electrolysis with polyoxometalate (POM) catalyst. (22nd April 2022) - Li, Mengzhu; Wang, Ting; Zhao, Mengyun; Wang, Yifan
Abstract: Converting corn straw into high-value chemicals and H2 energy is of great significance to the effective utilization of biomass resources. Based on the proton exchange membrane electrolysis technology, a circular electrolysis system for H2 evolution and corn straw degradation was built using polyoxometalate (POM) catalysts as redox media and charge carriers. Under mild conditions (80 °C), the influence of factors such as reaction temperature, reaction time, catalyst concentration, and current density on the research system was explored. As a result, the efficient use of corn straw has been realized. The degradation rate of corn straw was as high as 63.48%, and the Faraday efficiency of H2 production by electrolysis reaches 94.54%. The degradation products of corn straw were characterized and analyzed by SEM, FT-IR, XPS, GC-MS, and 2D HSQC NMR. This technique provides a potentially new pathway for H2 production and corn straw processing. Highlights: Corn straw resources could be converted to H2 and high-value chemicals. The Faraday efficiency of hydrogen production reaches 94.54%. As a redox medium and charge carrier, POM can be recycled. The operating voltage of the corn straw-POM system could be as low as 0.5 V".